PREVALENCE OF CHEWING TOBACCO AND ARECA-NUT USE AMONG PATIENTS ATTENDING DENTAL OPD AND ASSOCIATED ORAL MUCOSAL LESIONS. : J Peop Univ Med Health Sci. 2025:15(3), 114-123. http://doi.org/10.46536/jpumhs/2025/15.03.666 - Sana Javed1, Surwaich Ali Channa2, Waheed Murad Dahri3, Aneela Faisal Memon4, Ariba Jalbani5, Mahrukh6, Arhama Surwaich7 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Chewing tobacco (smokeless tobacco) and areca nut (Areca catechu derivative) are widely consumed psychoactive substance in South Asian region, including Pakistan. OBJECTIVE: To determine the prevalence of chewing tobacco and areca-nut use among patients attending dental hospital and associated oral mucosal lesions METHODS: This descriptive cross sectional study was carried out at Oral biology department of Bhittai Dental and Medical College Mirpurkhas from April 2024 to September 2024. Individuals of chewing tobacco and areca nut users, aged 18 years or older of either gender who visited the dental OPD for routine dental examinations or treatment were included. After taking demographic information patients underwent a comprehensive intraoral examination under adequate lighting, and review the medical record to assess the oral lesions. Expected lesions were further evaluated using toluidine blue staining and, where clinically indicated, subjected to incisional biopsy for histopathological confirmation. All patients were interviewed about their chewing tobacco and areca nut consumption habits, including the type of product used frequency, quantity, and duration of use. Data entry and analysis was done by SPSS version 23. RESULTS: Total of 139 participants were studied, with most aged 31–60 years (49.6%) and predominantly male (56.8%). Gutka was the most commonly used substance (66.2%), followed by mainpuri (12.9%), a mix of betel and tobacco (8.6%), betel nut (7.2%), and naswar (4.3%). Over half of the users (55.4%) had been consuming these products for less than one year, while 36.0% reported use for more than five years. Pigmentation was the most common lesion (84.9%), among gutka users, followed by white patches (48.9%, p=0.027) and ulcers (36.0%, p=0.001). Erosive lesions (28.8%) and growths (24.5%) were also significantly associated with tobacco chewing p 0.001. additionally, white patches linked with oral submucous fibrosis (48.9%), whereas OSF features (20.9%) and other OPMDs (8.6%) did not show significant associations (p->0.05), while only 14.4% of participants had no mucosal changes (p=0.054). CONCLUSION: Gutka observed as the most commonly used smokeless tobacco product, predominantly among middle-aged males, with a considerable proportion using it for prolonged duration. Chewing of Tobacco observed significantly linked to oral lesions, particularly pigmentation, white patches, ulcers, and erosive changes. However, the findings highlighted the urgent need for targeted awareness, early screening, and preventive strategies to reduce the burden of oral potentially malignant disorders in high-risk populations.